(untitled) (World Bulletin of Management and Law, 2024)
For improved quality management, many firms are now favoring the adoption of integrated management systems (IMS). This is demonstrated by the fact that many firms employed the ISO 9001 quality standard, ISO 14001 environmental standard, and OHSAS 18001 occupational health and safety management system as the foundation for the IMS, which was extensively adopted. It is also necessary to identify the management system that improves the effectiveness of IMS, which is the link between quality management and risk management. Consequently, as part of integration, the risk management system ISO 31000 was also given. The organization must suggest new standards and procedures in the current competitive climate due to mounting stakeholder or customer demands and pressure. The advantages of integration, convergent components of management systems, and implementation strategies are presented and discussed in this study. Eight specialists in the subject were interviewed in-depth as part of a series of interviews, and the data gathered was qualitatively assessed. The findings include the identification of sixteen implementation-related criteria for IMS and the application of the PDCA technique for an efficient IMS implementation. In summary, the study suggests integrating four management systems (ISO 9001, ISO 14001, OHSAS 18001, and ISO 31000) and utilizing the IMS to organize the quality management process towards sustainable practices inside the company